Relation of powers in gymnastics in the pre-olympic season in light of international sanctions against russian athletes - Pakholkova, N. V.; Somkin, A. A.; Zarodnyuk, G. V.; Larionova, M. N. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to conduct a comparative analysis of the results shown by the strongest national teams at the 2023 World Championships and Russian gymnasts at the Russian Cup to determine competitiveness in the international arena under sanctions.